Profiles of self-efficacy among cirrhotic patients in northern Guizhou Province, China: a latent profile analysis - Chengde Su; Chengde Su; Chengde Su; Qianqian Zhu; Qianqian Zhu; Qianqian Zhu; Mingdan Li; Mingdan Li; Yali Xu; Qian Liu; Qian Liu; Ying Zhang; et al. (Frontiers in Medicine, 2025)
ObjectiveTo explore the distinct profiles and influencing factors of self-efficacy in patients with liver cirrhosis via latent profile analysis (LPA) to provide evidence for the development of targeted interventions.MethodsThis was a single-center, cross-sectional study in which convenience sampling was used to recruit hospitalized cirrhotic patients between March and November 2024 from the Department of Infectious Diseases of a tertiary general hospital in Zunyi, Guizhou Province. Data were collected via four validated instruments: the General Information Questionnaire, the Chronic Disease Management Self-Efficacy Scale, the Self-Management Behavioral Scale for Patients with Cirrhosis, and the Social Support Rating Scale. Latent profile analysis (LPA) Mplus 8.3 and univariate and multivariate logistic regression analyses were performed via SPSS 26.0.ResultsA total of 260 questionnaires were distributed, with 257 valid responses collected, resulting in a response rate of 98.85%. Three distinct self-efficacy profiles were identified: low (7.39%), moderate (31.91%), and high (60.70%). Residence (OR = 0.055, 95% CI: 0.006–0.528), self-management score (OR = 0.846, 95% CI: 0.729–0.981), and social support score (OR = 0.655, 95% CI: 0.537–0.800) were significant predictors (p < 0.05).ConclusionThere was significant heterogeneity in the self-efficacy level of patients with liver cirrhosis. Healthcare professionals should provide targeted interventions addressing their specific needs on the basis of the distinct self-efficacy profiles of patients to increase self-efficacy levels and improve the quality of life of this population.